From the «transhumanism» to the «trasumanar». Dante and the recuperation of Philosophy - Monterde Ferrando, Rafael (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The object of this article is the study and comparison of the transhumanism of Julian Huxley and the trasumanar of Dante Alighieri. Although they are authors separated in time, they are connected by the fact that Dante’s transumanar inspired the formulation of the word with which Huxley defined his philosophy, transhumanism. In this way, Dante’s thought is traversed throughout the article until we reach, later, that of Huxley with the aim of comparing them and verifying the anthropological scope of both philosophical proposals.